Mongolia education sector fact sheet. (Metro Manila, Philippines Asian Development Bank, 2017)
While Mongolia has made significant achievements in expanding access to education, ensuring its quality and relevance remains a major challenge.
Keywords: Education -- Mongolia; Environmental economics -- Developing countries; Electronic books